Jump performance enhancement induced by countermovement - Hirayama, K. (Sports Performance, 2015)
The execution of a countermovement prior to the main movement, during which the agonist muscles experience a stretch-shortening cycle (shortening after being lengthened) enhances the exercise performance outcome (countermovement effect). During the stretch-shortening cycle, the fascicles and tendons exhibit a unique behavior; much of the length changes of skeletal muscle occur in tendons while fascicles contract almost isometrically. The countermovement effect varies among individuals and changes through training (or practice). The dynamics of muscle fascicles and tendons may underlie the effects of interindividual differences and training on the countermovement effect.